Formação docente para a educação infantil: Uma análise das percepções de acadêmicos do Curso de Pedagogia (UFPA) - FERREIRA, João Diego da Silva (2020)
This article is the result of a research on teacher training for Early Childhood Education and an analysis of the perceptions of the UFPA pedagogy course. The purpose of this study was to analyze the perceptions of pedagogical scholars regarding teacher education for the performance of Early Childhood Education. The study was qualitative, carried out through interviews with five undergraduates of the UFPA Pedagogy Course, defined with convenience sampling. Thus, the instrument used to obtain the information was semi-structured questions directed to the students. In addition, to analyze the data, we used Content Analysis (BARDIN, 2009) with NVIVO 10 software. The results highlight the diversified vocabulary of words and valuable concepts for the students of the Pedagogy Course such as Early Childhood Education, children, teaching, teacher , work, fundamental, internship, experience and so on. On the other hand, we have the knowledge of twenty that are more connected with the educational area such as Education (2.19%), Children (1.48%), Children (0.92%), Education